Optimisation of breast cancer patients' follow‐up – potential way to improve cancer care in transitional countries. (5th May 2016) - Bošković, L.; Gašparić, M.; Petrić Miše, B.; Petković, M.; Gugić, D.; Ban, M.; Jazvić, M.; Dabelić, N.; Belac Lovasić, I.; Vrdoljak, E.
Abstract : The aim of this analysis was to evaluate adherence of Croatian oncologists to follow‐up criteria as suggested by the current national and international guidelines for women with breast cancer receiving adjuvant endocrine therapy. The use of clinical and diagnostic methods was documented in this prospective, non‐interventional, multicenter study. A total of 438 post‐menopausal patients receiving adjuvant endocrine treatment with non‐steroidal aromatase inhibitors were included. Average annual frequency for each clinical and diagnostic method was calculated. Median adjuvant endocrine treatment duration before study recruitment was 10.5 months (interquartile 4.7–26.6). Patients were followed up for an average 23.5 ± 4.9 months. Average number of oncological visits was 5.3. Mammograms were performed at mean annual frequency of 0.7, chest radiographs at 0.5, abdominal ultrasounds at 0.9, breast ultrasounds at 1.2, complete blood counts and chemistry panels at 1.7, carcinoembryonic antigen at 0.8, cancer antigen 15‐3 at 1.6, gynaecological examination at 0.3, and densitometry at mean annual frequency of 0.3. In conclusion, among post‐menopausal women with breast cancer receiving adjuvant endocrine therapy in this study, more unnecessary and unproven follow‐up procedures were done compared to the guidelines' recommendations.